Smoking, alcohol, and analgesics in dyspepsia and among dyspepsia subgroups: lack of an association in a community. - Talley, N J (1994)
Dyspepsia is common in the general population, and despite a paucity of data, smoking, alcohol, and analgesics are believed to be important risk factors. The role of these environmental factors in subjects with uninvestigated dyspepsia was evaluated in a representative population sample. An age and gender stratified random sample of residents of Olmsted County, Minnesota, aged 20 to 64 years was mailed a valid self report questionnaire; 77% responded (n = 1644). Age and gender adjusted (1990 US white population) prevalence rates for dyspepsia (defined as frequent pain located in the upper abdomen, or nausea in the absence of a history of peptic ulcer disease) were calculated. Logistic regression analysis was used to estimate the association between dyspepsia and potential risk factors. The age and gender adjusted prevalence (per 100) of dyspepsia in the community was 21.8 (95% confidence interval 19.6, 23.9). Dyspepsia was significantly more common in younger subjects and females. Adjusting for age and gender, paracetamol (odds ratio (OR) = 2.2), aspirin (OR = 1.8), and smoking (OR = 1.5), but not alcohol (OR = 0.9), were associated with dyspepsia (all p < 0.05). When non-gastrointestinal somatic complaints were included in the logistic models, however, these environmental factors were no longer significant (OR = 1.3, 1.1, 1.2 and 0.9, respectively). Similar results were obtained when ulcer-like, dysmotility-like, and reflux-like dyspepsia were considered separately. The results were not significantly changed when subjects with a history of ulcer disease were included in the analyses. Smoking, alcohol, and analgesics may not therefore be important risk factors for dyspepsia in the community.